Molecular identification for Helicoverpa spp. in Bt and non- Bt crops in central Argentina - Balbi, Emilia Ines (2022)
The objective of this work was to identify, by molecular analysis, the species of the genus Helicoverpa in corn, soybean, and lucerne Bt and non-Bt crops, in central Argentina. A total of 1,343 carterpillars were analyzed by PCR-RFLP. Helicoverpa zea was the only species detected on non-Bt and on most Bt corn hybrids. The species H. gelotopoeon predominated on non-Bt soybean and on lucerne, and H. zea larvae occurred in low proportion. Bt soybean did not show Helicoverpa spp. infestations. The exotic H. armigera was not found, though adult moths of this species were light-trapped in a complementary sampling.